2008
DOI: 10.1183/09031936.00063207
|View full text |Cite
|
Sign up to set email alerts
|

European reference equations for CO and NO lung transfer

Abstract: The aim of the present study was to calculate reference equations for carbon monoxide and nitric oxide transfer, measured in two distinct populations.The transfer factor of the lung for nitric oxide (TL,NO) and carbon monoxide (TL,CO) were measured in 303 people aged 18-94 yrs. Measurements were similarly made in two distant cities, using the single-breath technique. Capillary lung volume (Vc) and membrane conductance, the diffusing capacity of the membrane (Dm), for carbon monoxide (Dm,CO) were derived.The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
113
3
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 34 publications
8
113
3
4
Order By: Relevance
“…Using 2.42 instead of 1.97 would have decreased Dm and increased Vc by 23%, and thus introduced an unlikely discrepancy between the two measurements. We therefore preferred to use 1.97 as previously reported in our reference equations (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using 2.42 instead of 1.97 would have decreased Dm and increased Vc by 23%, and thus introduced an unlikely discrepancy between the two measurements. We therefore preferred to use 1.97 as previously reported in our reference equations (3).…”
Section: Discussionmentioning
confidence: 99%
“…The coefficient relating DLNO and Dm was set at 1.97 according to the solubility and molecular weights of both gases (3). To solve the Roughton and Forster equation (37), we used an equation proposed by Forster (17) expressing the conductance of CO with hemoglobin ( CO) as a function of capillary PO2:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact as breath hold time is increased, NO expiratory concentration reduces, reaching the detection limit of the NO analyser. This is an issue when using electrochemical sensors, as we 1 and others did, 2,5,8 and not with a highsensitivity chemiluminescence NO analyser as other authors did. 10,11 As regards the membrane diffusion for carbon monoxide (DmCO), membrane diffusion for nitric oxide (DmNO) and capillary volume (Vcap), we prefer to call the capillary volume Vcap and not Vc as frequently done to avoid confusion with the vital capacity, and we do not agree with the Zavorsky and Borland critique.…”
mentioning
confidence: 97%
“…However, we recognise that our DLNO values in normal subjects, obtained in a sizeable number of subjects, are lower than those previously reported by Zavorsky et al 2 In any case the apparatus we used (Jaeger/Vyasis PFT Masterscreen) was calibrated for gas analysis using automated procedures and the linearity of analysers was factory checked. The formula used is: Concerning breath hold time, we used 4 s, which is the same as Aguilaniu et al 8 used whose data were the basis of the normal standards for European equations for carbon monoxide (CO) and nitric oxide (NO). Anyway, with a longer breath hold time we would expect an underestimation of DLNO, as reported by Dressler et al, 9 and not an overestimation as suggested by Zavorsky and Borland.…”
mentioning
confidence: 99%